Characterization of SNAREs determines the absence of a typical Golgi apparatus in the ancient eukaryote Giardia lamblia - Elías, Eliana Vanina (2008)
Giardia is a eukaryotic protozoal parasite with unusual characteristics, such as the absence of a morphologically evident Golgi apparatus. Although both constitutive and regulated pathways for protein secretion are evident in Giardia, little is known about the mechanisms involved in vesicular docking and fusion. In higher eukaryotes, soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs) of the vesicle-associated membrane protein and syntaxin families play essential roles in these processes. In this work we identified and characterized genes for 17 SNAREs in Giardia to define the minimal set of subcellular organelles present during growth and encystation, in particular the presence or not of a Golgi apparatus. Expression and localization of all Giardia SNAREs demonstrate their presence in distinct subcellular compartments, which may represent the extent of the endomembrane system in eukaryotes. Remarkably, Giardia SNAREs, homologous to Golgi SNAREs from other organisms, do not allow the detection of a typical Golgi apparatus in either proliferating or differentiating trophozoites. However, some features of the Golgi, such as the packaging and sorting function, seem to be performed by the endoplasmic reticulum and/or the nuclear envelope. Moreover, depletion of individual genes demonstrated that several SNAREs are essential for viability, whereas others are dispensable. Thus, Giardia requires a smaller number of SNAREs compared with other eukaryotes to accomplish all of the vesicle trafficking events that are critical for the growth and differentiation of this important human pathogen.